Tradisi Arab di Masa Nabi: dalam Perspective Teori Change and Continuity - Wargadinata, Wildana (el Harakah: Jurnal Budaya Islam, 2003)
The interesting attraction between local traditions and Islamic teachings has occurred since the earliest period in the history of Islamic civilization. The teachings of Islam, born as the most spectacular social revolution of the Middle Ages, still provide a loose space for local tradition. This kind of phenomenon becomes a study in writing about the Arab tradition in the time of prophethood. In the theory of Change and Continuity can be seen the element of very high flexibility in Islamic teachings. Elements are very important in the course of the development of Islamic da'wah in the future. The success of the spread of Islam can not be separated from this element. This does not mean that Islam has no identity. Islam in addition to having an element of flexibility also has a device of eternality. There is a central teaching that becomes the core of his teaching can not be mixed or modified. Tarik menarik antara tradisi lokal dengan ajaran Islam telah terjadi sejak masa yang paling dini dalam sejarah peradaban Islam. Ajaran Islam yang lahir sebagai sebagai revolusi sosial yang paling spektatuler pada abad pertengahan temyata masih memberi ruang gerak yang longgar pada tradisi lokal. Fenomena semacam inilah menjadi kajian dalam tulisan tentang tradisi Arab pada masa kenabian. Dalam teori Change and Continuity dapat dilihat adanya unsur fleksibilitas yang sangat tinggi dalam ajaran Islam. Unsur sangat penting dalam perjalanan perkembangan dakwah Islam ke depan. Keberhasilan penyebaran Islam tidak terlepas dari unsur ini. Hal ini tidak berarti Islam tidak memiliki jati diri. Islam di samping memiliki unsur fleksibilitas juga memiliki perangkat eternalitas. Ada ajaran pokok yang menjadi inti ajarannya tidak bisa dicampur aduk atau dimodifikasi.